Rethinking Devolution: Challenges for Aboriginal Resource Management in the Yukon Territory - Natcher, David C.; Davis, Susan (Society & Natural Resources, 2007)
After decades of state administration, indigenous peoples throughout the world are now succeeding, to varying degrees, in the reimplementation of self-governing institutions and administrative processes. This reorientation has been most observable in the context of natural resource management, where a major policy trend has been to devolve state authority and administrative responsibility directly to local levels. While the language of devolution and local control now permeates local–state interaction, in many cases the new institutions that have been created following devolution have little resemblance to indigenous forms of management. In this article, we present some of the institutional and ideological factors that continue to influence the way in which lands and resources are managed by First Nations in the Yukon Territory of Canada. In doing so, we identify the difficulties of applying indigenous cultural ideals into a management process that continues to be derived from non- indigenous values and principles.